Pengaruh Model Problem Based Learning dengan Pre-Learning Reading terhadap Kemampuan Berpikir Kritis Siswa - Santoso, Herto; Maulana, Maulana; Hanifah, Nurdinah (Jurnal Pena Ilmiah, 2019)
This research is motivated by the lack of critical thinking skills of elementary school students. Problem Based Learning (PBL) models with Pre-Learning Reading were chosen as a solution to improve students' critical thinking skills. The purpose of this study was to determine the improvement of critical thinking skills through PBL models with pre-learning reading; knowing the improvement of critical thinking skills through conventional learning; knowing the level of difference in critical thinking between students who study with the PBL model with pre-learning reading and students with conventional learning; knowing students' responses to PBL models with pre-learning reading. The design of this study was quasi-experimental with nonequivalent control group design. The instruments used were questions of critical thinking skills and student response questionnaires. The results of the study show that the PBL model with pre-learning reading and conventional learning can improve critical thinking skills, in terms of improving critical thinking skills, PBL models with pre-learning reading are better than conventional learning and students in the experimental class respond positively to use of the Problem-Based Learning model with Pre-Learning Reading.